2011
DOI: 10.1002/tax.602006
|View full text |Cite
|
Sign up to set email alerts
|

Origin and distribution of autopolyploids via apomixis in the alpine species Ranunculus kuepferi (Ranunculaceae)

Abstract: The evolution of polyploids is strongly influenced by their mode of origin. Autopolyploidy is often hampered by disturbances of chromosome pairing and segregation at meiosis, while allopolyploids exhibit fewer meiotic problems and potentially have selective advantages because of hybridity. Apomixis, the asexual reproduction via seed in flowering plants, can overcome problems of meiotic reduction, favouring range expansions of polyploids. We elucidate the origin and genetic structure of apomictic cytotypes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
63
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 63 publications
3
63
1
Order By: Relevance
“…Second, the extremely low frequencies of private AFLP bands found in the diploid northern Andean range (0.5%), the southern part of the Andean range (0%), and the southern populations of the Sierras de Cordoba (0.5%) in the study of Hensen et al (2011) indicate that there was no additional parental gene pool involved in the evolution of the tetraploids. Similarly low frequencies of private AFLP fragments have been reported for the autotetraploid Ranunculus kuepferi by Cosendai et al (2011). Thus, while other scenarios such as allopolyploid formation followed by long-distance dispersal or extinction of some parent populations are also conceivable, on current evidence we consider an autopolyploid origin to be more likely.…”
Section: Discussionmentioning
confidence: 56%
“…Second, the extremely low frequencies of private AFLP bands found in the diploid northern Andean range (0.5%), the southern part of the Andean range (0%), and the southern populations of the Sierras de Cordoba (0.5%) in the study of Hensen et al (2011) indicate that there was no additional parental gene pool involved in the evolution of the tetraploids. Similarly low frequencies of private AFLP fragments have been reported for the autotetraploid Ranunculus kuepferi by Cosendai et al (2011). Thus, while other scenarios such as allopolyploid formation followed by long-distance dispersal or extinction of some parent populations are also conceivable, on current evidence we consider an autopolyploid origin to be more likely.…”
Section: Discussionmentioning
confidence: 56%
“…In sexual autopolyploids, profound difficulties may arise during chromosome segregation at meiosis due to the increased complexity of pairings among doubled and therefore identical chromosome sets, which mostly pair as multivalents. An efficient segregation of such multivalents in case of autotetraploid R. kuepferi remains difficult (Cosendai et al , 2011). Common segregation issues within enlarged chromosome sets can lead to disadvantageous irregularities such as aneuploidy (Birchler et al , 2007; Ozias-Akins and Van Dijk, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…However, these studies did not quantify pathways of seed formation, and hence could not test for statistical correlations to geographical distances, elevation and related environmental parameters. Population genetic studies suggested autopolyploid origin (Cosendai et al , 2011), a high genotypic diversity and lack of geographical structure among tetraploids (Cosendai et al , 2013). Self-fertility of tetraploids supported the assumption of Baker’s law that rapid colonization could have played a role in distributions (Cosendai et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cosendai et al 2011). The diploids analyzed here contradict these findings: apomictic diploids are not purely the result of recurrent interspecific hybridization; however, triploid apomictic lineages may be recurrently derived from 2xApo-2xSex hybridization.…”
Section: A Conceptual Model For the Genetic Control Of Apomixis In Bomentioning
confidence: 99%